Study on the Aquaculture of Large Yellow Croaker in the Coastal Zone of Zhejiang Province Based on High-Resolution Remote Sensing - Jie Yin; Lina Cai; Jiahua Li; Xiaojun Yan; Beibei Zhang (Remote Sensing)
This study applied high-resolution satellite data to address the siting and evaluation challenges for potential cage aquaculture areas of large yellow croaker in Zhejiang Province. A typical template of water environmental factors for large yellow croaker cage aquaculture was developed, incorporating various environmental parameters and considerations that were not fully addressed in previous studies. This paper established the Site Selection Method for Large Yellow Croaker potential aquaculture (SSM-LYC) based on the template. Site selection and grading evaluation of potential cage aquaculture areas were performed using SSM-LYC. The findings include the following: (1) Potential aquaculture sites for large yellow croaker include 11 areas with water depths of 15–60 m along the coast of Zhejiang Province from 27° to 31° north latitude, of which 7 are in water depths of less than 40 m, and 4 are in water depths of 40–60 m. (2) Assessment and scoring for potential aquaculture sites were performed, pinpointing 4 central locations of first-level aquaculture areas offering scientific evidence for the feasibility of deep-sea aquaculture of large yellow croaker along the Zhejiang coast. (3) The conclusions drawn from this research provide significant guidance for future aquaculture strategies and regional planning. Moreover, SSM-LYC can be applied to other coastal waters in the world.